Delay and Lifetime Performance of Underwater Wireless Sensor Networks with Mobile Element Based Data Collection. (14th May 2015) - Janardanan Kartha, Jalaja; Jacob, Lillykutty
Abstract : Underwater Wireless Sensor Networks (UWSNs) may be easily partitioned due to resource constraints and sparse deployment, and such UWSNs need to be treated as Delay/Disruption Tolerant Networks (DTN). The principal objective of DTN routing is to maximize the possibility of eventual data delivery, which can be achieved only at the cost of high energy consumption and/or increased message latency. The energy efficiency and network lifetime are more important than data collection latency for certain underwater applications. We consider energy-efficient data collection using mobile elements, which is suitable for long-term sensing applications that are not time-critical. Using different analytical models, we investigate energy efficiency, network lifetime, packet delivery ratio, and message latency in a mobility-assisted data collection framework for UWSNs. The analytical models are validated with the experimental setup developed using the NS-2 based Aqua-Sim simulator. The results demonstrate that the proposed framework shows superior performance in terms of energy efficiency, network lifetime, and packet delivery ratio at the cost of increased message latency. The analytical models for delay performance are compared to see that the polling model is more effective in modelling the mobility-assisted data collection framework for UWSNs and more flexible in implementing different service policies.